Triple vessel injury with single penetrating trauma to the lower extremity requiring popliteal to posterior tibial artery bypass - Sandhu, Jaspreet (Trauma Case Rep, 2018)
This is a case report describing the delayed presentation of injury to all three lower extremity infrapopliteal arteries after a 34 year old male sustained multiple gunshot wounds, including one to his left lower extremity. As part of his initial assessment, ankle brachial index was performed and was found to be abnormal. Further work up for this was delayed due to need for emergent trauma laparotomy. After this procedure, more detailed evaluation with CT angiography of the extremity injury was performed. Though imaging indicated adequate perfusion of the lower extremity, serial neurovascular examination revealed inadequate perfusion. The patient required arterial reconstruction and fasciotomies. This case demonstrates the need for continued surveillance of extremity perfusion in atypical trauma cases when index of suspicion suggests the degree of injury may be worse than initial work up may indicate.